2009
DOI: 10.1152/japplphysiol.90949.2008
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal development of metabolic rate during normoxia and acute hypoxia in rats: implication for a sensitive period

Abstract: Liu Q, Fehring C, Lowry TF, Wong-Riley MTT. Postnatal development of metabolic rate during normoxia and acute hypoxia in rats: implication for a sensitive period. J Appl Physiol 106: 1212-1222, 2009. First published December 31, 2008 doi:10.1152/japplphysiol.90949.2008.-Previously, we reported that the hypoxic ventilatory response (HVR) in rats was weakest at postnatal day (P) P13, concomitant with neurochemical changes in respiratory nuclei. A major determinant of minute ventilation (V E) is reportedly the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
67
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(73 citation statements)
references
References 58 publications
6
67
0
Order By: Relevance
“…Another surprising finding from this study was that abrupt increases or decreases in pentobarbital resistance that we observed occurred mainly at P14, rather than at P11–P12 as elegantly demonstrated repeatedly by Wong-Riley and colleagues (Gao et al , 2011; Liu et al, 2006, 2009; Liu and Wong-Riley, 2002, 2004, 2005, 2006, 2010; Wong-Riley and Liu, 2008, Wong-Riley et al, 2013). We speculate that the abrupt changes in the medulla at P11–P12 may initiate a cascade of events that lead to further changes in the next two days that may compromise breathing.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Another surprising finding from this study was that abrupt increases or decreases in pentobarbital resistance that we observed occurred mainly at P14, rather than at P11–P12 as elegantly demonstrated repeatedly by Wong-Riley and colleagues (Gao et al , 2011; Liu et al, 2006, 2009; Liu and Wong-Riley, 2002, 2004, 2005, 2006, 2010; Wong-Riley and Liu, 2008, Wong-Riley et al, 2013). We speculate that the abrupt changes in the medulla at P11–P12 may initiate a cascade of events that lead to further changes in the next two days that may compromise breathing.…”
Section: Discussionsupporting
confidence: 74%
“…During acute hypoxia, the ventilatory response is weakest in P13 animals, and is significantly lower from P12–P14 compared to the rest of the first three postnatal weeks (Liu et al, 2006). At P13, the combination of relatively low metabolism, and low ratios of ventilation/O 2 consumption and ventilation/CO 2 production are hypothesized to be unique for the entire first 21 postnatal days and put the rats at risk during a severe, prolonged bout of hypoxia (Liu et al, 2009). Likewise, in a different laboratory, P12–13 male rats were found to have lower ventilation during hypercapnia (Holley et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These neurochemical changes are closely followed by significant increases in ventilation (Liu et al, 2006) and metabolic rate (Liu et al, 2009) at PND 13, which require too much energy to maintain under hypoxic conditions. This weakened hypoxic ventilatory response may explain why PND 14 rats were the most susceptible to the lethal effects associated with whole-body exposure to sarin.…”
Section: Discussionmentioning
confidence: 99%